Efficiency of Banks With a Double Bottom Line - Johann Burgstaller; Katharina Dietl (Credit and Capital Markets – Kredit und Kapital, 2023)
If banks' performance is to be be evaluated against the objectives they actually pursue, assessments of stakeholder-oriented banks should go beyond financial efficiency. Furthermore, also the environment these institutions operate in has to be kept in mind when interpreting levels of managerial inefficiency. For 401 Austrian regional banks, this study compares financial efficiency to a measure of social efficiency that considers several kinds of stakeholder benefits. Both efficiency scores are calculated by use of data envelopment analysis. In a second estimation stage, we use truncated regression to account for differences in efficiency due to the market environment. Our results show that efficiency rankings across Austrian savings banks and credit cooperatives change considerably when their double bottom line and local market factors are considered. Both issues thus are important for adequate and fair performance benchmarking.
Keywords: D22; G21; L20; M11; R51; 330; Savings Banks; Credit Cooperatives; Non-Profit Objectives; Social Efficiency; Data Envelopment Analysis